Does crime trigger genetic risk for type 2 diabetes in young adults? A G x E interaction study using national data. (November 2022) - Guo, Fangqi; Harris, Kathleen Mullan; Boardman, Jason D.; Robinette, Jennifer W.
Abstract: Background: Living in neighborhoods perceived as disordered exacerbates genetic risk for type 2 diabetes (T2D) among older adults. It is unknown whether this gene-neighborhood interaction extends to younger adults. The present study aims to investigate whether crime, an objectively measured indicator of neighborhood disorder, triggers genetic risk for T2D among younger adults, and whether this hypothesized triggering occurs through exposure to obesity. Methods: Data were from the Wave I (2008) National Longitudinal Study of Adolescent to Adult Health. A standardized T2D polygenic score was created using 2014 GWAS meta-analysis results. Weighted mediation analyses using generalized structural equation models were conducted in a final sample of 7606 adults (age range: 25–34) to test the overall association of T2D polygenic scores with T2D, and the mediating path through obesity exposure in low, moderate, and high county crime-rate groups. Age, sex, ancestry, educational degree, household income, five genetic principal components, and county-level concentrated advantage and population density were adjusted. Results: The overall association between T2D polygenic score and T2D was not significant in low-crime areas ( p = 0.453), marginally significant in moderate-crime areas ( p = 0.064), and statistically significant in high-crime areas ( p = 0.007). The mediating path through obesity was not significant in low or moderate crime areas ( ps = 0.560 and 0.261, respectively), but was statistically significant in high-crime areas ( p = 0.023). The indirect path through obesity accounted for 12% of the overall association in high-crime area. Conclusion: A gene-crime interaction in T2D was observed among younger adults, and this association was partially explained by exposure to obesity. Highlights: Genetic risk for type 2 diabetes is triggered by crime among young adults. The gene-crime interaction in type 2 diabetes is partially explained by obesity. Triggering effect of crime was examined in multiple ancestry groups.